2022
DOI: 10.21891/jeseh.1056832
|View full text |Cite
|
Sign up to set email alerts
|

Critical Thinking Dispositions as a Predictor for High School Students’ Environmental Attitudes

Abstract: This non-experimental quantitative study aimed to determine if high school students' critical thinking (CT) dispositions and environmental attitudes differ by gender, father, and mother's educational background and their CT dispositions are significant predictors of environmental attitudes. UF/EMI Critical Thinking Disposition Instrument and Environmental Attitude Scale were used to collect data in this study carried out with 139 high school students. It was found out that students' CT dispositions did not dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
2
6
0
1
Order By: Relevance
“…Results showed that the participants' critical thinking disposition in cognitive maturity, engagement and innovativeness were at high level in the five-point scale. These results were consistent with the previous studies (Bakır, 2022;Çağlı, 2022;Duncan et al, 2016;Erişti & Erdem, 2018;Orhan, 2022;Ulu & Baş, 2020). Considering that most of the pre-service teachers had a high cognitive maturity, it can be said that they can easily solve the problems they experience with stakeholders such as students, colleagues, school administrators and parents in different ways because they are aware of themselves and their environment.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 93%
“…Results showed that the participants' critical thinking disposition in cognitive maturity, engagement and innovativeness were at high level in the five-point scale. These results were consistent with the previous studies (Bakır, 2022;Çağlı, 2022;Duncan et al, 2016;Erişti & Erdem, 2018;Orhan, 2022;Ulu & Baş, 2020). Considering that most of the pre-service teachers had a high cognitive maturity, it can be said that they can easily solve the problems they experience with stakeholders such as students, colleagues, school administrators and parents in different ways because they are aware of themselves and their environment.…”
Section: Discussion Conclusion and Implicationssupporting
confidence: 93%
“…CT is considered one of the key competences of achieving sustainability [23] because it enables students to understand the state of the environment [24], analyze and solve environmental problems [25], and understand how new political, social, and economic structures and processes can lead us to sustainability [26]. More importantly, CT can empower students to question norms, practices, and opinions, reflecting on their values, perceptions, and actions as well as taking a position in the sustainability discourse [1], which will eventually allow them to participate in a democratic society [27].…”
Section: Education For Sustainable Development and Critical Thinkingmentioning
confidence: 99%
“…To begin, an environmental background scale was put in place to depict the awareness that high school students have about environmental issues. The scale was modeled from previous questionnaires that had been evaluated for both validity and reliability (Naim, 2019;Orhan, 2022). In addition, this scale was created to assess the environmental behaviors of speci cally high school students, which justi ed the choice.…”
Section: Questionnairementioning
confidence: 99%